2022
DOI: 10.7717/peerj.12959
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of iron deficiency anemia in Brazilian women of childbearing age: a systematic review with meta-analysis

Abstract: Background Iron deficiency anemia (IDA) is among the most common micronutrient deficiencies in women of childbearing age and may affect children’s development. Brazil has several national programs to tackle this condition, such as food fortification and supplementation for pregnant women, but IDA prevalence in this population has not been systematically reviewed. We sought to determine the prevalence of IDA in Brazilian women of childbearing age through a systematic review with metanalysis. Methodology A pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…A recent systematic review presented the prevalence of iron deficiency anaemia in Brazilian children under five years of age, but no pregnant women were evaluated [8]. In addition, a review published in 2022 showed the prevalence of 25% (95% CI [23][24][25][26][27][28], mainly in the North and Northeast regions (30%; 95% CI 24-37), of iron deficiency anaemia in women of childbearing age (a broader target audience than our review), highlighting that anaemia remains a public health problem in Brazil [65].…”
Section: Discussionmentioning
confidence: 79%
“…A recent systematic review presented the prevalence of iron deficiency anaemia in Brazilian children under five years of age, but no pregnant women were evaluated [8]. In addition, a review published in 2022 showed the prevalence of 25% (95% CI [23][24][25][26][27][28], mainly in the North and Northeast regions (30%; 95% CI 24-37), of iron deficiency anaemia in women of childbearing age (a broader target audience than our review), highlighting that anaemia remains a public health problem in Brazil [65].…”
Section: Discussionmentioning
confidence: 79%